NSCL in the ETSI M2M platform - Pegoraro, Ilan Emanuel Moreira (2015)
The evolution of every day gadgets into smart-devices able to react to their surrounding environment is enabling the development of novel applications aiming revolutionize the industry related to this technology. Currently much attention has been given to standardizing IoT and M2M in order to build an interoperable foundation that will enable the growth of the future Internet, where devices will communicate without, or at least minimizing, human intervention. In this dissertation is presented in first place issues such as: heterogeneity, scalability, addressing and the first approach taken by the ETSI M2M standard. Subsequently, is presented the ETSI M2M vision and high-level architecture together with current work in this area. Finally an implementation of the network middleware is going to be presented along with further testing.